Protocol for a feasibility and acceptability study using a brief ACT-based intervention for people from Southwest Wales who live with persistent pain - Madalina Saracutu; Darren J Edwards; Helen Davies; Jaynie Rance (BMJ Open)
Introduction Persistent pain affects a large percentage of the UK population and its burden has wide ramifications that affect physical, psychological, socioeconomic and occupational status. Pain has a significant impact on people’s well-being and quality of life. Some of the most common comorbidities found in this population are depression and anxiety and also maladaptive behaviours such as fear avoidance and catastrophising.Methods and analysis This is a protocol for a study assessing the feasibility and acceptability of a novel Acceptance and Commitment Therapy (ACT)-based intervention for people from Southwest Wales who live with persistent pain. A group of 12 participants will be recruited through the Health and Wellbeing Academy (Swansea University). After being referred by an Osteopath, and attending a brief meeting with the researcher, the participants will take part in six sessions over six consecutive weeks. ‘A Mindful Act’ is an ACT-based group programme aiming to teach people how to develop more acceptance and self-compassion, be more mindful and clarify personal values in order to live a more rich and meaningful life. The main outcomes will include the feasibility of the recruitment process and the measurement tools, the acceptability of the intervention for both the participants and the Osteopaths and the adherence to the programme. In order to measure acceptability of the intervention, qualitative interviews will be conducted to provide an insight into peoples’ experiences of taking part. Data will be analysed using Thematic Analysis, with the use of NVIVO 10. In addition, quantitative data will be collected at baseline, on completion of the programme and at 1 month and 3 months follow-up to reveal any differences in psychological flexibility, depression, anxiety, fear avoidance and general health status. The findings will help enhance the intervention by making appropriate modifications to the processes and procedures involved, following the recommendations made by the Medical Research Council framework. A larger scale study is envisaged to follow, in order to investigate the full effectiveness and cost-effectiveness of ‘A Mindful Act’.Ethics and dissemination This study was approved by the College of Human and Health Sciences Research Ethics Committee at Swansea University in December 2017. The findings will be disseminated through various means including: the first author’s PhD thesis, peer-reviewed journals as well as well as national and international conferences and public events.